Studi Tinjauan Teoritis: Pengaruh Kompetensi Kerja Terhadap Kinerja Karyawan Di Perusahaan - Wulan Auliyani; Dety Mulyanti (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
The company certainly has human resources as managers in organizing, managing and developing a strategic plan for the company's goals. In realizing these goals the most important thing is how the competence and performance of employees in the company. As an effort to improve employee performance, it must be supported by all components and the most important factor is increasing employee competence. The purpose of this theoretical review study is to find out how work competence influences the performance of employees in the company. The method used is a theoretical review by analyzing and comparing existing theories. The result of this theoretical review is that work competence greatly influences employee performance. The effect of competence on performance can be seen from the level of competence which has practical implications in human resource planning. It can be concluded that there is an influence of work competence on employee performance. The performance and effectiveness of employees in carrying out their duties is largely determined by competence. Companies are expected to always improve employee performance through training employees with their respective competency standards. This is because success in a company is influenced by the basic performance of employees obtained from the level of education, abilities and expertise possessed by these employees, so that they can contribute effectively and efficiently to the company.